METHOD OF AND APPARATUS FOR DETECTING BURIED PIPES - ASANO MINORU; YANAGIBASHI MINORU (2002)
PURPOSE: A pipe detecting apparatus and a method thereof are provided to detect the position of pipes precisely regardless of laying situation by trying searching pipes with varying frequency of electromagnetic wave and voltage and by detecting pipes with reflected wave image. CONSTITUTION: A pipe detecting apparatus includes a pulse generator(6), an electromagnetic wave control unit(7), an electromagnetic wave setting unit(8), an amplifier(9), a receiver(10), an image processing unit(11), and a display unit(12). Reflected waves of electromagnetic waves are processed to image, and reflected wave image is displayed on the display unit. Pipes are detected by varying frequency and voltage of electromagnetic wave, and detected by setting electromagnetic wave for checking pipes visually corresponding to reflected wave image. The position of the pipe is detected accurately and conveniently regardless of laying situation. 본 발명의 목적은 전자파의 반사파화상에 의한 매설관의 매설위치를 매설주위상황에 상관없이 정확하게 행할 수 있는 매설관 검출방법 및 장치를 제공하는 데에 있다. 이를 위하여 본 발명은 송신안테나(3)로부터 방사하는 전자파의 주파수(F)와 전압(A)을 가변으로 하여 매설관(2)의 탐색시험조작을 행하여 전자파의 반사파 화상에 의해 매설관을 식별할 수 있는 주파수와 전압의 전자파를 설정하여 매설관(2)의 탐색을 실행한다.